Effect of carbon numbers and structures of monosaccharides on the glycosylation and emulsion stabilization ability of gelatin. (30th September 2022) - Zhang, Yangyi; Xu, Jiamin; Zhang, Ting; Tao, Lina; Nie, Yinghua; Wang, Xichang; Zhong, Jian
Highlights: Bovine bone gelatins were modified by nine monosaccharides. Degrees of modification was dependent on monosaccharide carbon numbers. Secondary structure ratios depend on sugar carbon numbers and structures. Modification increased the droplet stability of fish oil emulsions at pH 3.0. 3C and 4C monosaccharides significantly inhibited emulsion liquid-gel transition. Abstract: Herein, the effect of saccharide glycosylation by nine monosaccharides on bovine bone gelatin for the stabilization of fish oil-loaded emulsions was explored. The gelatin modification was analyzed and then the emulsifying properties of monosaccharide-modified gelatins were analyzed at pH 9.0 and 3.0. The results demonstrated that glycosylated gelatin structure, droplet stability, creaming stability, and liquid-gel transition time were dependent on monosaccharide carbon numbers, monosaccharide structures, and solution pH. Glycosylation modification of gelatins did not obviously change the emulsion droplet stability at pH 9.0, whereas it increased the emulsion droplet stability at pH 3.0. Glycosylation modification of gelatins did not obviously change the emulsion creaming index values (5.1%–8.4% at pH 9.0 and 25.8%–33.1% at pH 3.0). Three-carbon and four-carbon monosaccharides glycosylation significantly increased emulsion liquid-gel transition times. This work provided useful information to understand the effects of carbon numbers and structures of monosaccharides on the protein modification.